First to File versus First to Use: Kajian Perlindungan Merek dalam Sengketa GoTo Gojek Tokopedia dan PT Terbit. - Nanakarani Priatma (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The trademark dispute between PT GoTo Gojek Tokopedia Tbk and PT Terbit Financial Technology has become a significant issue in the field of intellectual property law in Indonesia. This conflict arose because PT GoTo used the trademark name “GOTO,” which had already been officially registered earlier by PT Terbit. This study aims to examine the legal protection granted to registered trademark owners under Law Number 20 of 2016 concerning Trademarks and Geographical Indications, as well as to analyze the application of the first to file principle in resolving the dispute. This research employs a normative juridical approach by reviewing relevant legislation and conducting a case analysis based on the Decision of the Central Jakarta Commercial Court Number 71/Pdt.Sus-HKI/Merek/2022/PN Niaga Jkt.Pst. The findings indicate that Indonesia prioritizes the first to file system in determining trademark ownership, meaning that exclusive rights are granted to the party who registers the trademark first. The court decision in favor of PT Terbit confirms that formal registration serves as the primary legal basis for trademark protection. Therefore, this study highlights the importance of conducting trademark verification prior to public use and emphasizes the need to strengthen legal awareness among business actors to prevent similar disputes in the future.